EMPIRICAL STUDY OF THE PERFORMANCE OF THE ISLAMIC INVESTMENT - ALAOUI EL MRANI , DRISS; EL MEZOUARI, SAÏD (Revue du contrôle, de la comptabilité et de l’audit, 2020)
Sukuk is an investment certificate in line with the principles of Islamic finance. In the last decade, it has achieved higher growth in comparison to other segments in Islamic finance. The purpose of our article is to evaluate the performance of these instruments in an international context based on seven performance measurement models and to explore the possibility of diversification benefits between Sukuk indexes. The data used in our Study are the serie of Dow Jones Sukuk index for a period from September 2007 until December 2015. The results show that there is a weak significant correlation between Sukuk indexes, which does not hinder the possibility of diversification benefits.Secondly; the results also show that high quality Sukuk has outperformed the low quality Sukuk and this for the different performance measures of our study.In addition; the performance differs according to the rating of Sukuk.